Stair-climbing wheelchair with lever propulsion control of rotary legs. (17th June 2020) - Sasaki, Kai; Eguchi, Yosuke; Suzuki, Kenji
Abstract : This paper describes a novel stair-climbing wheelchair operated by human upper body using lever propelled rotary-legs with posture transition mechanism. The design principle of this wheelchair is to make use of the user's latent upper body capability, with appropriate mechanisms to enable extended functionality of the regular wheelchair without the need of heavy, expensive mechanisms or electric motors. An arm-operated mechanism allows the user to overcome steps and stairs independently without any external power source. The developed wheelchair consists of manual wheels with casters for planar locomotion, which provides capabilities equivalent to a regular manual wheelchair. In addition, the wheelchair has a rotary-legs mechanism based on lever propulsion control for climbing stairs. It also has a passive mechanism powered by gas springs for posture transition to shift the user's center of gravity between two positions for planar locomotion and for stair-climbing. The proposed design consists of only passive components, which makes the wheelchair more compact and lightweight. In this paper we describe in detail the development of this wheelchair and an investigation of how users can climb stairs independently. We also present evaluation experiments with a healthy participant and a dummy to investigate the feasibility of the proposed design. GRAPHICAL ABSTRACT: UF0001